O livro-jogo e o desenvolvimento da formação humana integral de estudantes da EJA EPT (PROEJA) - Beirouti, Mayara Romeiro Lins (2024)
Developed within the scope of the Graduate Program in Professional and Technological Education (ProfEPT) at the Federal Institute of Alagoas (IFAL), this research aimed to reflect on the relationship between students’ world knowledge and school knowledge in the EJA EPT (PROEJA) program, as well as the implications of this relationship for the comprehensive human development of these students. Situated within the Research Line “Educational Practices in Professional and Technological Education” and the Macroproject “Inclusion and Diversity in Formal and Non-formal Education Spaces in EPT,” the study is qualitative in nature, of the participatory type, with data collection instruments including questionnaires and interviews.The research participants were students in the first term, or module, of the Technical Course in Culinary Arts, in the EJA EPT modality, offered at IFAL, Marechal Deodoro campus. From a theoretical standpoint, the study was based on curriculum theories, integrated curriculum, and comprehensive human education. Based on the analysis of data obtained from interviews and questionnaires, it was identified that there are areas of knowledge not yet mastered by these individuals, and that such knowledge is not addressed in the school curriculum, despite the pedagogical work inherent to EJA EPT. The research culminated in the development of an Educational Product (EP), designed as a game-book, which will allow EJA students to access this knowledge — previously left out of their educational processes — and may contribute to the development of their comprehensive human education.